Early remodeling of müller cells in the rd/rd mouse model of retinal dystrophy. Issue 11 (4th June 2013) - Chua, Jacqueline; Nivison‐Smith, Lisa; Fletcher, Erica L.; Trenholm, Stuart; Awatramani, Gautam B.; Kalloniatis, Michael
Abstract: We studied the anatomical remodeling and gliosis of retinal Müller cells in the rd/rd mouse model of photoreceptor degeneration. A computational calculation of glutamine synthetase immunoreactivity was developed so we could specifically quantify changes in Müller cell anatomy between control mice (C57Bl/6) and the dystrophic strain. We found no change in the number of Müller cell somata between mice strains, indicating no cell proliferation as a function of development and degeneration. The retinal area occupied by the total Müller cell body (soma and processes) was significantly less in the rd/rd mouse retina compared with control mice. When only the outer retina was considered, we found rd/rd Müller cell processes were dramatically reduced during the cone phase of photoreceptor degeneration. However, at older ages an increase in Müller cell processes was seen. Conversely, glial fibrillary acidic protein (GFAP) expression showed a significant increase during cone degeneration followed by a reduction in older ages. Müller cell electrophysiology, particularly K + currents and membrane potential, was similar between rd/rd and control Müller cells during cone degeneration. Together, these results show that glial remodeling in the rd/rd retina follows separate phases—an initial conservative glial response involving the loss of Müller cells processes, hyperexpression of GFAP, and preservation of normal electrophysiology followed by an active growth of Müller cell processes, glial seal formation, and attenuation of GFAP expression after complete photoreceptor loss. J. Comp. Neurol. 521:2439–2453, 2013. © 2013 Wiley Periodicals, Inc. Abstract : In the rd/rd mouse, Müller cell processes are reduced in the outer retina during early degeneration but increase after total photoreceptor loss. Conversely, GFAP expression increases at early stages then decreases at older ages. Müller cell electrophysiology remains normal during early degeneration. Thus, rd/rd gliosis has an initial conservative response followed by active remodeling.